Business Management Strategies and Msmes Financial Performance with the Digitalization of Information Technology in the Times of the Covid-19 Skills - Marheni Marheni (Universitas Tidar, 2021)
The condition of MSMEs during the Pandemic requires MSMEs to have a business strategy to survive in the midst of the Covid-19 Pandemic. The purpose of this study is to describe the right strategy in managing the business and financial performance of MSMEs by implementing digitalization of technology during the Covid-19 pandemic. This research was conducted in Pangkal Pinang City, Bangka Belitung Islands. The population is all MSMEs in Pangkal Pinang City. The sampling method is purposive sampling. This type of research is descriptive research. Methods of data analysis using SWOT and PESTEL. Data analysis with SWOT is carried out by analyzing the strengths, weaknesses, opportunities and threats for MSMEs to increase their business in the midst of the COVID-19 Pandemic. The results show that the strategy of digitizing information technology is the right way to improve MSME business and finance during the Covid- 19 pandemic in Pangkal Pinang City. In addition, MSMEs must carry out a stability strategy in developing their business to survive the Covid-19 pandemic